Details Behind the Self‐Regeneration of Supported NiCo/Ce0.8Zr0.2O2 Bimetallic Catalyst in the CH4–CO2 Reforming Reaction. Issue 6 (11th April 2014) - Djinović, Petar; Črnivec, Ilja Gasan Osojnik; Erjavec, Boštjan; Pintar, Albin
Abstract Ceria zirconia solid solution with a high specific surface area and oxygen storage capacity was used to support NiCo bimetallic nanoparticles and was successfully employed as a catalyst in the methane–CO2 reforming reaction. During the reforming test with an equimolar CH4/CO2 ratio at 1023 K, an initial catalyst deactivation was observed, which was followed by a slow self‐reactivation. The catalyst reached its initial activity after approximately 400 h TOS with negligible carbon accumulation and H2 and CO yields of 71 and 85 %, respectively. Catalyst deactivation in the initial 25 h of reaction could be correlated to the oxidation of nanosized NiCo particles by water produced through the reversed water gas shift reaction pathway. With prolonged time on stream, sintering and growth of nanosized NiCo particles occurs, which makes them less susceptible to oxidation and slowly leads to their reduction and reactivation. In parallel, recrystallization of Ce0.8Zr0.2O2 support from cubic crystallites to a more irregular polyhedral shape occurs, which improves the oxygen storage capacity of the material and significantly contributes to the catalyst regeneration. The rate of catalyst regeneration mainly depends on the rate of Ce0.8Zr0.2O2 support recrystallization, which is driven by sintering, and is consequently much slower than the initial deactivation. Upon increasing the CH4/CO2 feed ratio to 1.5 and 2.33, water yields were significantly reduced and the previously observed catalyst deactivation could be strongly decreased or even completely avoided.